2016
DOI: 10.1186/s40064-016-3341-8
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the growth in the health sector and inbound health tourism: the case of Turkey

Abstract: One of the consequences of globalisation for Turkey, as well as in other emerging countries, has been an increasing trend in health tourism. Households have been considered choice the best option in terms of price and alternative possibilities while they have been solved their health problems. Previous studies have argued that the main drivers of the growth of inbound health tourism to developing countries are lower costs, shorter waiting periods, and better quality of care. This study aimed to test the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
2
10
0
3
Order By: Relevance
“…In terms of cointegration, it was found that the calculated F statistics are greater than the 5% simulated small sample upper bound critical values in all models leading to the rejection of the null hypothesis, and one can confidently conclude that demand for medical tourism and its determinants in Malaysia are cointegrated. Our results echo Uçak () for Turkey for a set of economic determinants. With respect to the long‐run estimator, Stock () documented that OLS estimation is super consistent and highly efficient.…”
Section: Resultssupporting
confidence: 84%
“…In terms of cointegration, it was found that the calculated F statistics are greater than the 5% simulated small sample upper bound critical values in all models leading to the rejection of the null hypothesis, and one can confidently conclude that demand for medical tourism and its determinants in Malaysia are cointegrated. Our results echo Uçak () for Turkey for a set of economic determinants. With respect to the long‐run estimator, Stock () documented that OLS estimation is super consistent and highly efficient.…”
Section: Resultssupporting
confidence: 84%
“…Beyond the payment for medical treatments, travelers also spend a considerable amount purchasing tickets and planning for accommodation in the destination country. According to a recent study conducted in Turkey, the per capita expenditures of inbound medical tourists are more than double the expenditures of other tourists [ 3 , 40 ].…”
Section: Considerations Regarding Cbrc and The Host Countrymentioning
confidence: 99%
“…In Turkey, in parallel with the Health Transformation Program, health tourism has rapidly developed in the last ten years. [15][16][17] Both public and private hospitals offer high quality services with the latest technology and highly qualified personnel. Forty-nine health care institutions have been accredited by the Joint Commission International (JCI) in Turkey, one of the highest rates in the region.…”
Section: Medical Tourism In Turkeymentioning
confidence: 99%